2022
DOI: 10.1152/ajpgi.00178.2021
|View full text |Cite
|
Sign up to set email alerts
|

A systems-level analysis of bile acids effects on rat colon epithelial cells

Abstract: Bile acid diarrhoea is a chronic condition caused by increased delivery of bile acids to the colon. The underlying mechanisms remain to be elucidated. To investigate genes involved in bile acid diarrhoea, systems-level analyses were employed on a rat bile acid diarrhoea model. Twelve male Wistar Munich rats, housed in metabolic cages, were fed either control or bile acid-mixed (1% w/w) diets for ten days. Food intake, water intake, urine volume, bodyweight and faecal output were monitored daily. After euthanas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Twenty-three genes included ANKRD40CL, CYP2W1, SLC51B, ISX, CA1, MMP28, CA12, ETNK2, UGDH, RASL12, CRYBG2, CPM, SLC4A4, and VPS13A, which were up-regulated, while CD6, TAP1, and SERPINB2 were down-regulated in both DAH vs. DAN and DAH vs. DLYH. It had been reported that the up-regulation of SLC51B expression inhibited the inflammatory response in the mouse colon, thus protecting against colonic mucosal injury, promoting bile acid transport, and maintaining the healthy homeostasis of the colonic mucosa [38,39]. The Intestine-specific homology cassette (ISX) is a homology cassette-containing protein belonging to a paired subfamily.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-three genes included ANKRD40CL, CYP2W1, SLC51B, ISX, CA1, MMP28, CA12, ETNK2, UGDH, RASL12, CRYBG2, CPM, SLC4A4, and VPS13A, which were up-regulated, while CD6, TAP1, and SERPINB2 were down-regulated in both DAH vs. DAN and DAH vs. DLYH. It had been reported that the up-regulation of SLC51B expression inhibited the inflammatory response in the mouse colon, thus protecting against colonic mucosal injury, promoting bile acid transport, and maintaining the healthy homeostasis of the colonic mucosa [38,39]. The Intestine-specific homology cassette (ISX) is a homology cassette-containing protein belonging to a paired subfamily.…”
Section: Discussionmentioning
confidence: 99%
“…Another feeding experiment was carried out by Yde et al 80 In this experiment, rats were fed for 10 days on a diet with added cholic acid, and this diet generated a total fecal bile acid concentration in the colon similar to the high level found in humans with irritable bowel syndrome with diarrhea. First, they found that the diet plus cholic acid appeared to cause activation of the nuclear bile acid receptor farnesoid X receptor (FXR) as well as activation of the membrane bound bile acid receptor TGR5.…”
Section: Progression To Colorectal Cancer: Dna Damage Mutation Epigen...mentioning
confidence: 99%
“…Notably, its effectiveness in alleviating diarrhea has been attributed to the modulation of water movement through the suppression of aquaporin 3 (AQP3) expression in the large intestine [12]. A recent report has also demonstrated that bile acids upregulate the expression of AQP3 in the rat colon [13]. In addition, there are reports indicating that bile acids regulate colonic motility and secretion relating to the development of diarrhea [14,15].…”
Section: Introductionmentioning
confidence: 99%